2015
DOI: 10.1016/j.dsr.2014.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Development of a deep-sea laser-induced breakdown spectrometer for in situ multi-element chemical analysis

Abstract: a b s t r a c tSpectroscopy is emerging as a technique that can expand the envelope of modern oceanographic sensors. The selectivity of spectroscopic techniques enables a single instrument to measure multiple components of the marine environment and can form the basis for versatile tools to perform in situ geochemical analysis. We have developed a deep-sea laser-induced breakdown spectrometer (ChemiCam) and successfully deployed the instrument from a remotely operated vehicle (ROV) to perform in situ multi-ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 161 publications
(71 citation statements)
references
References 80 publications
(111 reference statements)
0
69
0
2
Order By: Relevance
“…The excited atoms and ions emit specific wavelengths of light as they relax back to their ground state, which allows for simultaneous multi-element detection. LIBS is a promising tool for on-site chemical analysis and has been applied to the surveys of nuclear powers plants [1,2], planetary [3,4] and deep-sea explorations [5][6][7]. However, LIBS signals obtained underwater using a conventional single pulse method are significantly degraded compared to measurements in gaseous environments [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The excited atoms and ions emit specific wavelengths of light as they relax back to their ground state, which allows for simultaneous multi-element detection. LIBS is a promising tool for on-site chemical analysis and has been applied to the surveys of nuclear powers plants [1,2], planetary [3,4] and deep-sea explorations [5][6][7]. However, LIBS signals obtained underwater using a conventional single pulse method are significantly degraded compared to measurements in gaseous environments [8][9][10].…”
Section: Introductionmentioning
confidence: 98%
“…It has further been shown that well resolved spectra can be observed for both bulk liquids [17] and submerged solids [18] at pressures of up to 30 MPa with little effect of external pressure using a long-pulse technique. This method has been applied to in situ measurements of seawater and hydrothermal deposits at depths of more than 1000 m, using a 3000 m depth rated long-pulse LIBS device, ChemiCam [5]. The aim of this study is to investigate whether the signals obtained using the long-pulse technique are suitable for quantitative analysis.…”
Section: Introductionmentioning
confidence: 99%
“…In particularthe employment of high water pressure during laser ablation and the understanding of its role on the laser induced plasma and bubble dynamics can be used in different surveys such as geochemistryi nd eep ocean, [1] laser propulsion in water, [2] hydraulic machinery [3] biomedicine. In particularthe employment of high water pressure during laser ablation and the understanding of its role on the laser induced plasma and bubble dynamics can be used in different surveys such as geochemistryi nd eep ocean, [1] laser propulsion in water, [2] hydraulic machinery [3] biomedicine.…”
Section: Introductionmentioning
confidence: 99%
“…1-3 Especially, LIBS has a potential to be applied even to underwater environments, and the application to in-situ remote analysis at the bottom of the sea/lake is highly desired. [4][5][6][7][8][9][10][11] However, the emission spectra of the laser-induced plasma in water are severely deformed [12][13][14] due to the strong confinement effect on the plasma. [15][16][17] To overcome this problem, double-pulse or multi-pulse irradiation with a pulse interval of tens of microseconds 4,12,[18][19][20][21][22] and single long-pulse ($150 ns) irradiation 5, [23][24][25][26] have been investigated, and the use of such irradiation schemes have been found to improve the spectral features of atomic lines for underwater LIBS applications, i.e., narrow spectral lines are obtained.…”
Section: Introductionmentioning
confidence: 99%